SLC39A8/Zinc Suppresses the Progression of Clear Cell Renal Cell Carcinoma - Liu, Lilong; Hou, Yaxin; Hu, Junyi; Zhou, Lijie; Chen, Ke; Yang, Xiong; Song, Zhengshuai (Frontiers in Oncology, 2021)
Clear cell renal cell carcinoma (ccRCC) is the most frequent and lethal subtype, which has high risk of metastasis or recurrence, accounting for 75%~83% of renal cell carcinoma (RCC). Zrt‐ and Irt‐like proteins (ZIP) family members (SLC39A1-14) function to pass zinc into the cytoplasm for many critical biological processes when cellular zinc is depleted. However, the functional analysis of individual ZIP family genes in ccRCC are not clarified. This study aimed to investigate whether ZIP family genes are related to the clinicopathological features and survival of ccRCC patients, and to identify the function of key gene of ZIP family in ccRCC in vitro. Through bioinformatics analysis of tumor databases, SLC39A8 was identified as a key gene of ZIP family in ccRCC, which could be used as an effective indicator for diagnosing ccRCC and judging its prognosis. With the progression of tumor, the expression of SLC39A8 decreased progressively. The prognosis of patients with low expression of SLC39A8 is significantly worse. Furthermore, we found that overexpression of SLC39A8 or treatment with low concentration of zinc chloride could effectively inhibit the proliferation, migration and invasion of ccRCC cells. Moreover, the inhibition effect of SLC39A8 overexpression could be enhanced by low concentration zinc supplement. Therefore, this study provides a novel understanding for the role of SLC39A8/zinc in the regulation of ccRCC progression. These findings provide a new direction and target for progressive ccRCC drug development and combination therapy strategies.